Public Private Partnership as a Development Innovation in Sustainable Development - Fiulaizi, Anna; Lukman, Juwita Pratiwi (Universitas Negeri Makassar, 2025)
This study analyzes the evolution of research themes related to Public Private Partnership (PPP) using a bibliometric approach through three main visualizations: co-occurrence networks, word frequency over time, and thematic evolution. The analysis shows that PPP has increasingly occupied a strategic position in the discourse of public administration and development, marked by its relevance to themes such as planning, management, investment, and various aspects of governance. The rise of key terms such as public administration, public-private partnerships, and sustainable development since 2014 confirms that PPP has progressed from a technical issue of public service delivery toward a more complex and long-term cross-actor collaboration framework. The thematic evolution visualization shows a shift in research focus from management and planning topics toward issues of sustainability, urbanization, and collaborative governance. In the context of sustainable development, PPP serves as a mechanism that drives long-term investment, reduces gaps in service access, and supports the achievement of sustainable development. These findings provide a basis for future research agendas related to designing more adaptive, integrative, and inclusive partnership models. The study also recommends strengthening governance, transparency, and public participation in PPP implementation so that PPP functions not only as a financing solution but also as an engine of equitable and sustainable development transformation.